Effect of nickel doping into solder alloy and its strength between SnCu-Ni/immersion gold joint - Zetty Akhtar, Abd Malek (2017)
Flip chip assembly, which is well known as controlled collapse chip connection (C4) has been widely used in semiconductor industry. Solder acts as a joining material in flip chip to interconnect chip with substrate, in order to provide electrical and mechanical continuity in assemblies. Since selection of solder material is important in solder joint performance, one of the strategies to improve joint’s reliability is to add additional alloying elements to solder. Therefore, the effect of nickel doping or addition in SnCu and SnAgCu solder alloy was investigated in this study. Although SnCu and SnAgCu alloy are considered as promising alternative in developing lead free solder alloy, it showed an increased brittle interfacial fracture compared to SnPb solder under impact loading. Thus, adding element such as nickel to the alloy composition become one of the interesting issues in lead free solder studies, as it will further enhance the mechanical properties of the alloys and the reliability of solder joints. Furthermore, addition of nickel to solder alloy in this study also acts as a replacement of nickel coating that is commonly used as a barrier layer between solder and Cu substrate. The objective of this study is to examine the effect of various nickel percentage on intermetallic compound formation and growth, as well as solder joint strength. To develop SnCu-xNi solder alloy, commercial solder (Sn-0.7Cu) and nickel powder were placed in crucible before it is melted in furnace under temperature 425˚C to 450˚C for 40 minutes. The same procedure was used to develop SnAgCu-xNi solder alloy, but with the addition of 3.0 weight percent of silver powder to alloy composition. Nickel weight percentages that were used in this study are 0.05, 0.10, 0.20 and 0.25. The composition of both types of solder alloy was then confirmed using energy dispersive x-ray analysis. From analysis, two eutectic phases were detected in solder alloy which is tin and intermetallic Cu6Sn5. The weight percentages of nickel in solder alloy were also similar to the amount that had been introduced before melting process. Reflow process was then conducted between each type of solder and substrate coated with immersion gold at 250˚C for 25 minutes. Some specimens were then put to go through isothermal aging process in aging oven at temperature 150˚C for 250, 500, 1000 and 2000 hours respectively. Microstructures of solder joint for as reflow condition and after aging were observed using both optical microscope and field emission scanning electron microscopy. There are two types of intermetallic formed during reflow and aging processes, which are Cu3Sn and Cu6Sn5. Thickness of intermetallic for all joints increases with aging time, mainly due to Cu3Sn and Cu6Sn5 growth. Based on thickness measured, joints with 0.05 and 0.25 weight percentage gave desired intermetallic thickness compared to other joints. Besides that, growth rate of intermetallic compounds over aging time was calculated using Arrhenius relationship. Lap shear test is also performed according to standard ASTM D1002. The lap shear test results indicated that percentage of Ni addition in solder alloy (0.05 and 0.25 weight percentage) does affect the solder joint shear strength. Apparently, based on the result and discussion of this study, the weight percentage values of 0.05 and 0.25 were recommended to be doped in solder alloy.